Tracing the Influence of Sharia-Based Local Regulations on Students' Clothing in Public Schools - Rizkidarajat, Wiman; Mutahir, Arizal; Chusna, Aidatul; Taufiqurrohman, Muhammad (KnE Social Sciences, 2023)
Since the promulgation of Law Number 44 of 1999 concerning the Implementation of the Privileges of Aceh, almost all regions in Indonesia have enacted sharia regulations. This caused the penetration of Islamic values through legal regulations in the form of regional regulations. This paper aims to trace the influence of sharia-based local regulation in society through sociology and cultural studies, which is to refine the existent perspectives, such as a single sociological perspective or a single law perspective. The method used in this paper is juridical-sociological to obtain primary data from legislation and cultural studies and secondary data from previous research and phenomena. The finding of this paper is that the administrative defects of the legal content in the sharia-based regional regulations produce a sociological effect on one legal object, namely women in public spaces in the form of public schools. Furthermore, a newer hypothesis is also presented that stresses how regional regulations with sharia nuances leave permanent social effects on female students in public schools. Keywords: Sharia-based Regional Regulation, Discrimination, female students, Public Schools